Preschool Staff Spot Social Communication Difficulties, But Not Restricted and Repetitive Behaviors in Young Autistic Children - Nilsson Jobs, Elisabeth (J Autism Dev Disord, 2019)
To fulfill the criteria for autism spectrum disorder (ASD), symptoms must be present across domains and contexts. We assessed preschool staff’s ratings of social communication and interaction (SCI) and restricted and repetitive behaviors (RRBs) in 3-year-old siblings of children with ASD, either diagnosed (n = 12) or not diagnosed (n = 36) with ASD, and typically developing siblings with no family history of ASD (n = 16). Ratings of SCI were more accurate than RRBs in differentiating the ASD group from the two other groups, and only the SCI ratings correlated with clinical assessment of social behavior. We conclude that while preschool staff ratings of SCI behaviors are adequate, ratings of RRBs should be treated with more caution.